2015
DOI: 10.14260/jemds/2015/528
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Socioeconomic Factors to Reproductive Tract Infections and Infertility in Rural India

Abstract: OBJECTIVE:This study was designed to find out how socioeconomic, cultural, educational and religious factors play a role in causation of RTI/STD. STUDY DESIGN: This study was conducted at Gynae, OPD of Dist. Hospital Samba, Jammu, J&K. 200 patients coming for infertility checkup and treatment between Feb. 2013 to Jan. 2014 were included in the study. It was an observational cross -sectional study. A pretested, semi-structured questionnaire was administered which included information about demographic, socioeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…Previous studies also noticed a high level of gynaecological morbidities among sexually active [ 34 , 35 ]. This study deviates from previous studies in noticing the positive association between the use of sanitary napkins and a low level of gynaecological morbidities [ 36 , 37 ]. We are not sure about the mechanism of how this association was generated as we could not find any relevant literature; however, it could be presumed that the accumulation of blood in the genital area for a prolonged period may be a risk factor.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies also noticed a high level of gynaecological morbidities among sexually active [ 34 , 35 ]. This study deviates from previous studies in noticing the positive association between the use of sanitary napkins and a low level of gynaecological morbidities [ 36 , 37 ]. We are not sure about the mechanism of how this association was generated as we could not find any relevant literature; however, it could be presumed that the accumulation of blood in the genital area for a prolonged period may be a risk factor.…”
Section: Discussioncontrasting
confidence: 99%
“…The gynaecological morbidities were higher among adolescents who shared toilets than those adolescents who did not share toilets. A study highlighted higher gynaecological morbidities for those sharing toilets than those who do not share the toilet [ 36 ]. Sharing toilet seats may be a factor associated with high gynaecological morbidities [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 In a study conducted by Rana et al in Jammu and Kashmir, vaginal discharge (22%) and pain abdomen (13%) reported were almost similar to our study where vaginal discharge and abdominal pain were 21% and 15% respectively. 10…”
Section: Discussionmentioning
confidence: 99%